PENGARUH BIAYA PENJUALAN DAN INVENTORY TURNOVER TERHADAP NET PROFIT MARGIN PADA PERUM BULOG KANWIL BALI - indra, indra firmansyah; Satria, Muhammad Rizal; Purnami, Ni Nyoman Cintya (Universitas Logistik dan Bisnis Internasional, 2025)
Perum BULOG is one of the state-owned companies that operates in the food logistics sector. Perum BULOG in recent periods has experienced fluctuating profits, this can be caused by several factors, namely sales costs and inventory turnover. The phenomenon of scarcity of government rice supplies has led to an increase in rice prices which has become the center of public attention because it has caused a surge in demand for rice purchases but the lack of rice availability has made the public and the Indonesian Farmers Union question the performance of Perum BULOG. This is interesting for further research. The aim of this research is to determine the effect of sales costs and inventory turnover on net profit margin. This research uses quantitative methods with secondary data in the form of Perum BULOG's monthly financial reports for 4 years, namely the 2020-2023 period. The analysis techniques used are data normality test, product moment correlation analysis test, multiple correlation analysis test, multiple regression analysis test, coefficient of determination analysis test, partial hypothesis test (t test) and simultaneous (f test) using IBM SPSS Statistics 25. The results of the t test show that (X1) sales costs partially have no significant effect on the net profit margin, while (X2) inventory turnover partially has a significant effect on the net profit margin. The results of the f test show that simultaneously sales costs and inventory turnover have a significant effect on net profit margin.